Clinical Value of Serum S100A8/A9 and CA15-3 in the Diagnosis of Breast Cancer - Samaneh Khorrami; Masoumeh Tavakoli; Elahe Safari (Iranian Society of Pathology, 2019)
Background and Objective: S100A8/A9 is a heterodimer calcium-binding protein which is involved in tumor cell proliferation, adhesion and invasion, and is proposed as a biomarker for better diagnosis and prognosis in many cancers. The aim of this study was to evaluate the simultaneous serum-based level of S100A8/A9 and CA15-3 as well-illustrated cancer biomarkers, as well as their prognostic value in breast cancer patients and healthy matched controls. Material and Methods: Thirty breast cancer patients at different stages of disease and healthy matched controls with no history of inflammatory, autoimmune diseases, or cancer, were enrolled in the study. The levels of S100A8/A9 and CA15-3 were assessed serologically using the Enzyme-linked immunosorbent assay (ELISA) method, and the relevance of these markers with patients' clinicopathological features were subsequently assessed.  Results: Based on our data, the serum levels of both S100A8/A9 and CA15-3 were significantly higher in patients compared to the healthy controls, and thus positively correlated with tumor size. Also, statistical analysis shows that the serum level of S100A8/A9 has 100% specificity and sensitivity (AUC = 1.00, 95% CI) for the diagnosis of breast cancer patients. Conclusion: According to our data as well as other observations, the S100A8/A9 heterodimer can be considered as a potential biomarker for the proper diagnosis and prognosis of breast cancer.